LEGAL APPROACH TO IMPLEMENTING SECURITY MEASURES FOR COMBATTING THREATS TO NATIONAL CRITICAL INFRASTRUCTURES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The quality of life and security of all citizens, including all EU citizens, is closely related to the provision of essential services through interaction of different critical infrastructures. Cross sectoral measures are required to be implemented in order to obtain high level of protection and optimal minimisation of potential risks for critical infrastructures, as various potential risks could also affect national security. Taking into account the fact that the general framework on critical infrastructure sometimes could not sufficiently address all various challenges to critical infrastructures in each and every country, it is possible to consider complex legislative approach for implementation of security measures for combatting threats to national critical infrastructures. The current articles outlines the specifics of implementing legal approach in reference to combatting threats to national critical infrastructures in line with the EU regulatory framework and focusing also to Bulgarian national legal sources and practical challenges.